2017
DOI: 10.1515/jim-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Original Research. Candida in Oral and Maxillofacial Pathology: Clinical Findings and Risk Factors

Abstract: Background: Candida, and especially Candida albicans, colonizes the oral mucosa and becomes invasive when the immune system weakens. Therefore, frequently, oral and maxillofacial pathology can be associated with Candida. Objective: The qualitative and quantitative assessment of Candida colonization of the oral cavity in patients with oro-maxillo-facial conditions; to establish an association between the different contributing factors and colonization. Material and methods: Samples were collected from 70 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The candidiasis can be easily recognised, even if other clinical pictures could simulate the same aspect, as some syndromic conditions ( Marrelli et al 2012 ), some oncological lesions ( Santacroce et al 2005 , Petrovan et al 2017 ) or aggressive bacterial infections in immunocompromised patients or as results of infections from foreign bodies ( Inchingolo et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The candidiasis can be easily recognised, even if other clinical pictures could simulate the same aspect, as some syndromic conditions ( Marrelli et al 2012 ), some oncological lesions ( Santacroce et al 2005 , Petrovan et al 2017 ) or aggressive bacterial infections in immunocompromised patients or as results of infections from foreign bodies ( Inchingolo et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…from sputum can have clinical significance, in the context of a pulmonary aspergillosis. Development and progression of yeast infections in colonized (oral or vaginal) mucosa and to adjacent sites is possible, in the context of different favoring factors such as the use of antibiotics, alcohol intake, smoking or radiotherapy (5).…”
Section: Editorialmentioning
confidence: 99%
“…The study of Petrovan et al concluded that in oral and maxillofacial surgery increased Candida colonization can be expected, and as far as treatment is concerned, specific antifungal drugs should be considered. 5 Willing to show the link between oral conditions and premalignant disorders, the study of Monea et al focuses on the concomitant presence of desquamative gingivitis and periodontal health-related conditions. 6 Another study finds that children diagnosed with acute lymphoblastic Krisztina Mártha • Str.…”
mentioning
confidence: 99%